Conceptualizing Global Cloud Landscape: A Review Of Adoption Issues And Challenges - Hanifah, Abdul Hamid; Mokhtar, Mohd Yusof (Medwell Journals, 2016)
An adoption of cloud computing in the IS has changed the way the business is conducted in any organizations. This IT innovation has created a new phenomenon of Information Systems (IS) from a conventional IS to the cloud-serviced IS. Nevertheless, cloud adoption is not as fast as the dynamic changes in the technology itself due to its issues and challenges. This study seeks to theoretically conceptualize cloud computing innovation adoption from technological, organizational and people dimensions focusing on the cloud adoption challenges. Although, the technical solution is abundant, security has been and is still identified to be the most critical challenges from all dimensions. The future research will lead to cloud information security assessment from the human perspectives.